A study on prevalence of alcohol consumption among higher secondary school students in Theni district, Tamil Nadu - S., Shankareswari; B., Jayapriya; K., Sandeep; A., Lourdu Jafrin (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Studies show that in India, the health loss from alcohol will grow larger, unless effective interventions are implemented. Initiation of alcohol intake starts from a very early age and is higher in rural areas. The best way to reduce alcoholism is prevention rather than curing the already addicted persons. For this we need to know the magnitude of this problem. This study is aimed at estimating the prevalence, identifying the causative and contributing factors of alcoholism among higher secondary school children of Theni district. Methods: A self-administered validated questionnaire was given to the male school students of 15 to 17 years (XI and XII students) to assess the prevalence and pattern of alcohol use among them. The questionnaire was prepared with reference from the global school-based student health survey (GSHS), the alcohol use disorders identification test (AUDIT) questionnaire and the cut-annoyed-guilty- eye (CAGE) questionnaire. Data analysis was done using software OpenEpi, Version 3. Results: A total of 500 students were analyzed with a response rate of 94% (n=470). The overall prevalence of alcohol use was found to be 31.06%. Nearly 70% had the possibility of alcoholism and should be investigated further for severity of alcohol use, 30% had impaired control over drinking almost daily and 17% had injury or injured someone because of drinking. Conclusions: The mean age of initiation of alcohol consumption is decreasing and the number of alcohol consumers is increasing.